Systém na dávkování CO2 - Hrudička, Aleš; Hrudička Aleš (České vysoké učení technické v Praze, 2017)
Tato práce se zabývá detekcí koncentrace CO2 ve vodní nádrži a následnou regulací této koncentrace. První část pojednává o metodách měření a možnostech regulace CO2 v komerční sféře. Také je zde popsána pH elektroda jako hlavní senzor v dané problematice. V další části je navrženo zařízení pro detekci a regulaci koncentrace CO2. Součásti této práce je také ověření funkčnosti zařízení.

This thesis deals with a detection of CO2 concentration in water tank and a regulation of this concentration. First part describes methods of measurement and possible options for CO2 regulation in commercial spaces. There is also a description of pH electrode as the main sensor in this matter. In the next part a device for detection and regulation of CO2 is designed. Part of this thesis is also a verification of the device's functioning.
System for CO2 dosing
Keywords: měření CO2,pH elektroda,elektromagnetický ventil,Arduino; CO2 measurement,pH electrode,electromagnetic valve,Arduino